The Phenomenon of Hallyu or Korean Wave in Shaping Gen-Z Consumption Interest - Ahmad , Maudi Meliani; Alamsyah, Indra Fajar; Abdurrahim Abi Anwar, Umari (UNISBA Press, 2024)
Abstract. This research focuses on the global impact of a country's culture, as seen in the Korean Wave or Hallyu phenomenon. This phenomenon not only attracts consumption, but also indirectly shapes the lifestyle of its fans. The purpose of this research is to explain the Korean Wave phenomenon in the formation of cultural identity, describe the role of South Korean celebrities in influencing consumptive behaviour, and develop the role of generation Z in supporting the creative industry in Bandung City. The method used is qualitative data analysis with a transcendental phenomenological approach according to Moustakas (1994). Data collection techniques included in-depth interviews, observation, and document review. The data source of this research is generation Z who are fans of Korean dramas with a total of 9 people using purposive sampling technique. The data analysis techniques used were data reduction, data presentation, and verification. This research found that the Korean Wave influences generation Z's cultural identity, shapes consumptive behaviour, and contributes to the growth of the creative industry. This research provides input for generation Z to improve entrepreneurship education, collaboration between young entrepreneurs, and digital skills development to capitalise on the potential of the Korean Wave and support local economic growth. Abstrak. Penelitian ini berfokus pada dampak global budaya suatu negara, seperti yang terlihat pada fenomena Korean Wave atau Hallyu. Fenomena ini tidak hanya menarik minat konsumsi, tetapi juga secara tidak langsung membentuk gaya hidup para penggemarnya. Tujuan penelitian ini adalah untuk menjelaskan fenomena Korean Wave dalam pembentukan identitas budaya, mendeskripsikan peran selebriti Korea Selatan dalam memengaruhi perilaku konsumtif, serta mengembangkan peran generasi Z dalam mendukung industri kreatif di Kota Bandung. Metode yang digunakan adalah analisis data kualitatif dengan pendekatan fenomenologi transendental menurut Moustakas (1994). Teknik pengumpulan data meliputi wawancara mendalam, observasi, dan tinjauan dokumen. Sumber data penelitian ini adalah generasi Z yang merupakan penggemar drama Korea dengan total 9 orang menggunakan teknik purposive sampling. Teknik analisis data yang digunakan adalah reduksi data, penyajian data, dan verifikasi. Penelitian ini menemukan bahwa Korean Wave memengaruhi identitas budaya generasi Z, membentuk perilaku konsumtif, dan berkontribusi terhadap pertumbuhan industri kreatif. Penelitian ini memberikan masukan bagi generasi Z untuk meningkatkan pendidikan kewirausahaan, kolaborasi antar pengusaha muda, dan pengembangan keterampilan digital untuk memanfaatkan potensi Korean Wave dan mendukung pertumbuhan ekonomi lokal.